P754 Short-term and long-term outcome for dilation therapy of stricturing Crohn's disease of the small intestine using balloon-assisted endoscopy - a combined analysis of 1194 endoscopic balloon dilation procedures. (16th January 2018) - Bettenworth, D; Bokemeyer, A; Lopez, R; Rieder, F
Abstract: Background: Strictures are a common complication of Crohn's disease (CD) and may develop in all segments of the gastrointestinal (GI) tract. While colonoscopy has been proven suitable and effective for balloon dilation therapy of CD-associated strictures of the ileocecal, the published evidence on efficacy and safety of balloon-assisted endoscopy (BAE) for balloon dilation therapy of CD strictures of the small intestine is scarce. We therefore performed a combined efficacy and safety analysis based on all published studies of BAE for small intestinal strictures available in the literature. Methods: A formal systematic literature review was performed to assess all relevant citations found in Embase, Medline and the Cochrane library regarding BAE used for EBD of small intestinal stricture. In addition, conference proceedings including Digestive Disease Week 2010–2017, European Crohn's and Colitis Foundation 2011–2017, United European Gastroenterology Week 2013–2016, Advances in IBD 2015–2017, American College of Gastroenterology 2016–2017, German Gastroenterology Congress 2013–2017 were screened for additional data. Available technical and clinical variables were extracted from all studies available for a descriptive pooled data analysis. Weighted efficacy averages were calculated for sub-groups. Results: In total, 19 publications with a total of 468 CD patients and 1194 performed dilation procedures were included. 19.3% were anastomotic strictures. Technical success rate was 88.1%, resulting in clinical efficacy in 78% of patients. Major complications with regard to dilation, defined as perforation, bleeding or dilation-related surgery, occurred in 3.7% of all procedures. During a median follow-up period of 19 months, 47.1% of patients reported symptomatic recurrence, while 40.1% of patients needed to undergo re-dilation and 28.8% required surgical intervention. Currently, there is no study available investigating the impact of concomitant therapeutic approaches such as steroid injection, cutting techniques or stent placement on the outcome of BAE EBD for small-bowel GI strictures in CD patients. Conclusions: BAE for dilatation therapy of CD-associated strictures of the small intestine possesses a high rate of short-term technical and clinical success and may represent an alternative to surgery in stricturing CD. BAE-associated complication rates appear comparable to those related to dilation therapy of ileocecal strictures during colonoscopy. Larger, controlled studies are warranted to further evaluate BAE for dilation therapy of CD strictures of the small intestine.